0617 Working Memory and Psychomotor Vigilance Performance After Brief Naps in Hypersomnolent Patients: MSLT Correlates. (27th April 2018) - SAINI, P; Bremer, E; Broyles, S; Rye, D; Trotti, L
Abstract: Introduction: Physiologic sleep inertia is operationalized as cognitive impairments upon awakening. Markedly pronounced sleep inertia, or sleep drunkenness, is common in idiopathic hypersomnia. Previous work has demonstrated significant worsening of vigilance on Psychomotor Vigilance Task (PVT) lapses (reaction times>500ms), reciprocal of reaction time (RRT) and slowest 10% of RRT associated with nap length and accrued sleep length among hypersomnolent patients during MSLT. A differential sensitivity of various cognitive processes to sleep inertia may be a significant contributing factor to these complaints such as working memory. Methods: Patients undergoing PSG/MSLT (N=37; Age=36.42 ± 14.14; 81.09% women), with diagnoses of Idiopathic hypersomnia (n=17), Obstructive Sleep Apnea (n=7), Narcolepsy Type 1 (n=3) and Type 2 (n=2), KLS(n=1) and subjective sleepiness with normal MSLT (n=7) were administered PVT before and after MSLT naps 2 and 4 and 0-back and 3-back N-Back tasks before and after nap 3. Accuracy on the N-Back was defined as correct classification rate of targets and non-targets. PVT and N-back performance was analyzed with repeated-measures ANOVA and post-hoc t-tests. Results: For Nap 4, lapses, RRT, and S-RRT demonstrated significant worsening post-nap relative to pre-nap, (10.47 ± 19.29(pre) vs 15.01 ± 21.15(post), t=2.02, p=0.05); (3.36±.85(pre) vs 2.93 ± 1.01(post), t=-3.97, p=0.0003); (2.03±.79(pre) vs 1.73±.80(post), t=-3.27, t=0.0018), respectively. Nap 4 sleep time, sleep efficiency and accumulated sleep through 4 naps (except for lapses) was significantly associated with lapses, Mean RRT and Mean S-RRT. Accuracy on the 3-Back demonstrated significant improvement post-nap relative to pre-nap, (.61±.25(pre)vs.71±.21(post), t=3.92, p=.0004), and associated with Nap 3 sleep efficiency (B=-.13, SE=.05, p=.011). Similar results for 0-Back accuracy (.78±.27(pre)vs.88±.18(post), t=3.93, p=.0004), and association with Nap 3 sleep efficiency (B=-.14, SE=.04, p=.0008). Reaction Times(ms) for 3 and 0-back demonstrated similar improvement, (1143.36 ± 452.52(pre)vs.1091.06 ± 470.83(post), t=-2.90, p=.006) and (840.11 ± 366.5(pre)vs 832.15 ± 383.3(post), t=3.93, p=.0004), respectively; with 0-back associated with sleep efficiency (B=-.14, SE=.04, p=.0008). Conclusion: Depreciation of psychomotor vigilance is consistent with previous findings, while improvements in working memory performance suggests discriminating the effects and sensitivities of sleep inertia from benefits of sleep-consolidation requires multiple WM tasks in addition to the N-back. Support (If Any): This work was supported by the National Institutes of Health undergrants K23 NS083748 (LMT) and R01 NS089719 (DBR); and the MindScience Foundation (DBR).